Ab initio study of the vibrational properties of crystalline TeO2: The alpha, beta, and gamma phases - Ceriotti, M; Pietrucci, F; Bernasconi, M (2008)
Based on density functional perturbation theory, we have studied the vibrational properties of three crystalline phases of tellurium dioxide: paratellurite alpha-TeO2, tellurite beta-TeO2, and the new phase gamma-TeO2, recently identified experimentally. Calculated Raman and IR spectra are in good agreement with available experimental data. The vibrational spectra of alpha- and beta-TeO2 can be interpreted in terms of vibrations of TeO2 molecular units.